Medium‐Energy Electron Detector Onboard the FY‐3E Satellite - Yu‐Guang Ye; Jia‐Wei Li; Cong Huang; Hong Zou; Qiu‐Gang Zong; Xiao‐Xin Zhang; Jin‐Song Wang; Ying Liu; Yong‐Fu Wang; Xiang‐Qian Yu; Wei‐Hong Shi; Hong‐Fei Chen; et al. (Space Weather)
Abstract The Medium‐Energy Electron Detector (MEED), a space weather monitoring instrument on the Fengyun‐3E (FY‐3E) satellite, is introduced in this paper. The MEED utilizes pin‐hole imaging technology on low‐orbit satellites for medium‐energy electron detection. Two orthogonal sensor heads enable the MEED to measure electrons from 18 directions simultaneously in the energy range of 30–600 keV (divided into eight exponentially distributed energy channels). The instrument has a ∼12° angular resolution and covers two 180° × 30° fields of view. With the magnetometer onboard the same satellite, the pitch angle distribution of medium‐energy electrons can be obtained with good angular resolution. This paper presents the design principle, ground calibration results, and preliminary on‐orbit test results of the FY‐3E MEED. The on‐orbit test results show that the medium‐energy electron fluxes, geographical distribution, energy spectrum, and pitch angle observed by the MEED are in agreement with the expected results. The MEED provides a new method to observe the low‐orbit energetic electron radiation environment from the FY‐3E satellite. Its successful in‐orbit operation will enable the theoretical study of radiation belts and improve space weather research.